2007
DOI: 10.1093/jac/dkm113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metronidazole on growth and toxin production by epidemic Clostridium difficile PCR ribotypes 001 and 027 in a human gut model

Abstract: Duration of cytotoxin production by C. difficile ribotype 027 markedly exceeds that of ribotype 001. Sub-optimal gut concentrations of metronidazole, possibly due to inactivation by components of normal gut flora, are associated with continued toxin production. These findings may help to explain the increased severity of symptoms and higher case-fatality ratio associated with infections due to C. difficile ribotype 027.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
69
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 31 publications
7
69
1
2
Order By: Relevance
“…1B). This inability to recover metronidazole has been previously noted (18), and it has been suggested that inactivation of metronidazole by human gut microbiota such as enterococci may be responsible for the lack of activity (19,20).…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…1B). This inability to recover metronidazole has been previously noted (18), and it has been suggested that inactivation of metronidazole by human gut microbiota such as enterococci may be responsible for the lack of activity (19,20).…”
Section: Resultsmentioning
confidence: 62%
“…Although vancomycin and metronidazole (both antibiotics) and lacticin 3147 (a member of the lantibiotic class I bacteriocins) are all active against C. difficile (15,17,18), their relative antimicrobial activity has not been compared to date. To address this issue, the ability of these three broad-spectrum antimicrobials to control C. difficile ribotype 001 was assessed using a model of the distal colon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Las esporas de C. difficile son resistentes a todos los antimicrobianos conocidos, principalmente debido a que son metabólicamente inactivos y a que la membrana interna es impermeable a la difusión de moléculas pequeñas, lo que impide el ingreso de antimicrobianos hacia el núcleo de la espora [84][85][86][87] . Los principales antibacterianos utilizados en el tratamiento de las IACD son metronidazol, vancomicina y recientemente fidaxomicina 88 .…”
Section: Resistencia De Esporas De C Difficile a Antimicrobianosunclassified
“…Los principales antibacterianos utilizados en el tratamiento de las IACD son metronidazol, vancomicina y recientemente fidaxomicina 88 . Estudios in vitro han demostrado que, tanto metronidazol como vancomicina, no inhiben la formación de esporas de C. difficile 84,85 , lo que es consistente con las elevadas tasas de recurrencia de IACD observadas en estudios clínicos 89 . En contraste, fidaxomicina, a concentraciones sub-inhibitorias, inhibe la formación de esporas de C. difficile in vitro 42 , y los estudios clínicos han demostrado que reduce a la mitad los episodios de recurrencia de IACD, comparado con vancomicina 41,90 , debido posiblemente a la inhibición de la formación de esporas durante el tratamiento.…”
Section: Resistencia De Esporas De C Difficile a Antimicrobianosunclassified